2024
DOI: 10.1088/1402-4896/ad2898
|View full text |Cite
|
Sign up to set email alerts
|

Yield–stress shear thinning and shear thickening fluid flows in deformable channels

Ashish Garg,
Pranjal Prasad

Abstract: Yield stress shear thinning/thickening fluids flow through flexible channels, tubes are widespread in the natural world with many technological applications. In this paper, analytical formulae for the velocity profiles and flow rate are derived using the Herschel--Bulkley rheological model in both rigid and deformable shallow channels, employing the lubrication approximation. To account for deformable walls, the approach outlined by \citet{gervais2006flow} and \citet{christov2018flow} is utilized, applying sma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The results gathered from these simulations collectively support the idea that even in highly narrow CNTs with a diameter as small as 1.66 nm, the flow of water behaves following the slip-modified Hagen-Poiseuille relation. Interestingly, the actual flow rates they observed were higher than what we would expect based on the traditional no-slip Hagen-Poiseuille relation [29][30][31], where water sticks to the tube walls. However, their theory failed to support the claims made by Majumder et al [15] and Holt [32,33] in their previous studies, where they suggested that water behaves very differently in these nanotubes.…”
Section: Introductionmentioning
confidence: 79%
“…The results gathered from these simulations collectively support the idea that even in highly narrow CNTs with a diameter as small as 1.66 nm, the flow of water behaves following the slip-modified Hagen-Poiseuille relation. Interestingly, the actual flow rates they observed were higher than what we would expect based on the traditional no-slip Hagen-Poiseuille relation [29][30][31], where water sticks to the tube walls. However, their theory failed to support the claims made by Majumder et al [15] and Holt [32,33] in their previous studies, where they suggested that water behaves very differently in these nanotubes.…”
Section: Introductionmentioning
confidence: 79%
“…Their MD simulations consistently support the notion that water flow within nanochannels adheres to the slip-modified Hagen-Poiseuille relation. This finding is particularly interesting because it suggests higher flow rates compared to those predicted by the traditional no-slip Hagen-Poiseuille relation [16][17][18], which assumes water molecules stick to the channel walls. Also, Israelachvili [13] experimentally calculated the viscosity of tetradecane and water between two mica sheets placed at distances lower than 50 Å and proposed that the viscosity of water/tetradecane can be calculated using…”
Section: Introductionmentioning
confidence: 82%
“…Also, the shear stress τ xz is acting along the negative x direction on both the surfaces DD ′ C ′ C and AA ′ B ′ B. Dropping the xz notation from the stress, the force balance can be written as [30,31]…”
Section: D Planar Modelmentioning
confidence: 99%